Occupational cholangiocarcinoma diagnosed 18 years after the end of exposure to 1,2-dichloropropane and dichloromethane at a printing company: a case report - Masahiko Kinoshita; Yasunori Sato; Hiroko Nebiki; Yutaka Tamamori; Naomi Ishii; Takeshi Inoue; Genya Hamano; Akishige Kanazawa; Shoji Kubo (Surgical Case Reports, 2019)
Abstract Background Cholangiocarcinoma due to exposure to 1.2-dichloropropane (DCP) or dichloromethane (DCM) is classified as occupational cholangiocarcinoma. We report a case of occupational cholangiocarcinoma diagnosed 18 years after the end of exposure to organic solvents at a printing company. Case presentation A 41-year-old man presented to our hospital with jaundice and anorexia. He had previously worked for 6 years at a printing company where an outbreak of occupational cholangiocarcinoma occurred and was exposed to high concentrations of organic solvents during his employment. Computed tomography demonstrated lower bile duct obstruction by the bulky nodal metastasis at the hepatoduodenal ligament with upstream biliary dilatation, an intraductal papillary tumor in the dilated left superior lateral bile duct (B2), and enlargement of the periaortic nodes. Clinical diagnosis of an unresectable invasive intraductal papillary neoplasm of the bile duct (IPNB) with extensive nodal metastasis was made. Although chemotherapy and laparoscopic gastrojejunostomy were performed for the duodenal obstruction, the patient died due to rupture of the tumor. Pathological examination of the autopsy specimen revealed well-differentiated adenocarcinoma at the stromal site along Glisson’s sheath in segment 3, an IPNB lesion without invasion in B2, and biliary intraepithelial neoplasia and chronic bile duct injury at various sites in the large bile ducts. The bulky lymph node (poorly differentiated adenocarcinoma with partial squamous cell differentiation) invaded the bile duct and duodenum. Conclusions We report a case of occupational cholangiocarcinoma that developed 18 years after the end of exposure to DCP and DCM. Long-term follow-up is required to carefully survey development of cholangiocarcinoma in workers with an occupational history of exposure to organic solvents.